2014
DOI: 10.1590/0103-6440201302426
|View full text |Cite
|
Sign up to set email alerts
|

Self-Perceived Oral Health Influences Tooth Brushing in Preschool Children

Abstract: This study assessed the influence of socioeconomic and clinical factors, as well as parent's perception of child's oral health on the toothbrushing frequency of 0-5-year-old children. The study was carried out in Santa Maria, RS, Brazil, during the National Children's Vaccination Day, and 478 children aged 0-5 years were included. Data were collected by clinical examinations and a structured questionnaire, conducted by 15 calibrated examiners and 30 supports. A questionnaire was filled out by the parents with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 18 publications
(25 reference statements)
0
11
0
4
Order By: Relevance
“…Los niños de uno a cinco años tuvieron una mayor frecuencia de no cepillado que los de seis a 12 años, tendencia reportada anteriormente por otros estudios (16,17) , esto podría ser atribuido a que los niños en esa edad requieren de ayuda para cepillarse y sus padres pueden no estar conscientes de ello y restarle importancia al cepillado en la dentición decidua (18) . El porcentaje de no cepillado fue mayor en aquellos no atendidos en un servicio odontológico dentro de los seis meses previos, similar a lo reportado en un estudio de niños mexicanos de seis a 12 años, que reportó una mayor probabilidad de cepillado frecuente en aquellos que recibieron atención odontológica en los 12 meses previos al estudio (19) .…”
Section: Discussionunclassified
“…Los niños de uno a cinco años tuvieron una mayor frecuencia de no cepillado que los de seis a 12 años, tendencia reportada anteriormente por otros estudios (16,17) , esto podría ser atribuido a que los niños en esa edad requieren de ayuda para cepillarse y sus padres pueden no estar conscientes de ello y restarle importancia al cepillado en la dentición decidua (18) . El porcentaje de no cepillado fue mayor en aquellos no atendidos en un servicio odontológico dentro de los seis meses previos, similar a lo reportado en un estudio de niños mexicanos de seis a 12 años, que reportó una mayor probabilidad de cepillado frecuente en aquellos que recibieron atención odontológica en los 12 meses previos al estudio (19) .…”
Section: Discussionunclassified
“…Therefore, the presence of bacterial biofilm increases the chance of the outcome. Such finding suggests that good habits and especially the quality of oral hygiene can reduce the severity of the disease (20,21). However, isolated plaque control measures and guidance directed are admittedly inadequate, since socioeconomic conditions were pointed out as distal determinants of the development of caries, modulating the exposure to risk and protection factors, in addition to the oral health services (22).…”
Section: Discussionmentioning
confidence: 99%
“…A study of 478 parents who were asked to categorize their child’s oral health as better or worse than that of other children of similar age found that parents who perceived their child’s oral health was worse or equal to the other children’s oral health reported a lower frequency of tooth brushing when compared with those who possessed a more positive perception. 16 …”
Section: Discussionmentioning
confidence: 99%